Hubungan Stress Level Dan Mekanisme Koping Dengan Smoking Behaviour Pada Remaja Pertengahan Di SMA X Kota Bandung - Nataliya, Yuhana; Tambunan, Dior Manta (Universitas Murni Teguh, 2024)
Smoking behavior is a person's activity as a response to a stressful stimulus that influences his or her actions to carry out smoking activities. The aim of this research was to determine the relationship between stress levels and coping mechanisms with smoking behavior in middle adolescents in X Senior High School at Bandung City. The objective of this study is to identify the relationship of stress level and Coping mechanism with smoking behaviour on middle adolescent. The research method is Quantitative with cross sectional design. The population in this research was all 300 children in their middle adolescents who attended.The sampling technique was random sampling. The number of samples in this study was 171 respondents using the Slovin formula. Data analysis used the Spearman Rho test and Manova test. The results of this research using the Spearman test show that there is a relationship between stress level and coping mechanisms and smoking behavior with p- value < 0.05. The Manova test explains that there is a relationship between stress level and smoking behavior with p-value <0.05. On the other hand, there is no relationship between coping mechanisms and smoking behavior with p-value > 0.05. It is recommended toconduct further research by adding social pressure variables.